Is dual sourcing a better choice? The impact of reliability improvement and contract manufacturer encroachment. (May 2021) - Dong, Binwei; Tang, Wansheng; Zhou, Chi; Ren, Yufei
Highlights: We study sourcing strategy choice under CM encroachment and reliability improvement. Without CM encroachment, the OEM prefers dual sourcing when the fixed ordering cost is small. The OEM facing CM encroachment may switch its sourcing strategy. Quality investment cost (initial yield rate) has a positive (negative) effect on dual sourcing performance. The competitive CM and the OEM incur a win–win situation under some specific conditions. Abstract: This paper investigates the strategic sourcing choice of an original equipment manufacturer (OEM) in the presence of contract manufacturer (CM) encroachment and reliability improvement. In the absence of CM encroachment, the OEM prefers dual sourcing when the fixed ordering cost is small. In contrast, faced with CM encroachment, the OEM may switch its sourcing strategy from single sourcing to dual sourcing as the level of competition increases. Moreover, a higher reliability investment cost enhances the OEM's propensity to choose dual sourcing strategy. Furthermore, the OEM is more likely to choose a single sourcing strategy when the initial yield rate is higher. Under certain specific conditions, both the competitive CM and the OEM are better off when the OEM chooses the single (dual) sourcing strategy, thereby establishing a win–win situation.